Primacy effects in the formation of opinions on an unfamiliar environmental topic: Experimental evidence from mineral exploration and mining - Olga Poluektova; Hannah Julienne; Deirdre A. Robertson; Aoife K. Braiden; Pete Lunn (The Economic and Social Research Institute (ESRI), 2022)
Transitioning to the green economy relies on new developments that may negatively affect people's localities and involve certain risks. This study investigates how people form opinions about such developments, using mineral exploration and mining as an example. A representative sample (N=1000) participated in a pre-registered online experiment where they were exposed to information supporting or opposing mining. We recorded a strong primacy effect: the information participants read first biased subsequent opinion. This effect was reinforced when people read counterargument that integrated information about both risks and benefits of mining and when they made a public stance.
Keywords: 330; primacy effect; opinion formation; environment; climate crisis; energy crisis; place attachment